The Influence of Healthcare Service Quality and Hospital Reputation on Patient Loyalty: The Mediating Role of Patient Experience - Rahmah, Mirhamida; Purnama, Chamdan; Fatmah, Dinda; Hasani, Syaiful; Rahmah, Yusriyah; Rahmah, Zakiyah Zulfa (International Journal of Economics, Management and Accounting, 2026)
This study explores how healthcare service quality, hospital reputation and brand, and patient experience influence patient loyalty, emphasizing the mediating role of patient experience. Control variables such as gender, education level, and type of health insurance were also considered. The research was conducted at a hospital in East Java and involved 165 inpatients aged 18 years and over. It was analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that patient experience is the strongest determinant of loyalty, followed by healthcare service quality, hospital reputation, and brand. Among the control variables, education level was found to have a significant impact on patient loyalty, whereas gender and type of health insurance had a limited effect. The analysis shows that hospital reputation and brand play a crucial role in shaping patient experience, which mediates the impact of both on patient loyalty. The model demonstrates strong predictive relevance, explaining variance in both patient experience and loyalty, indicating its robustness in capturing these dynamics. However, the cross-sectional design of the study and its focus on a single hospital limit the generalizability of the results and the ability to capture temporal changes. Future research should be conducted in multiple healthcare settings and adopt longitudinal designs to explore additional factors, such as socioeconomic and cultural influences. This research contributes to the field by emphasizing the importance of hospital reputation and brand, healthcare service quality, and educational level in fostering patient loyalty, and by providing actionable insights for improving patient-centered care through strategic enhancements to experience and service delivery.